Analisis Strategi Digital Marketing Melalui Aplikasi Sosial Media Pada Toko Fashion Nonashope di Sangatta Kabupaten Kutai Timur - Dewi Rifta Dayanah; Rizqi Ramadhani; Muhammad Ridho; Riska Febriana (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
The fashion industry has been one of the sectors most affected by the digital revolution. Fashion stores, including Nonashope stores in Sangatta, have felt the significant impact of this change. With increasing online competition, digital marketing strategies are key maintaining and increasing market share. One of the most frequently used digital marketing strategies is social media. In the ever-evolving digital era, the role of social media in marketing has become increasingly important. Social provides a powerful platform to interact with potential customers and expand brand reach. This study aims to investigate the effect of digital marketing strategies through social media used by Nonashope Stores in Sangatta. It is important for them to understand how digital marketing strategies on these platform affect business performance. This research uses a qualitative method with interviews with the owner and customers of the Nonashope fashion store. The result showed that digital marketing strategies through social media had a significant impact on brand awareness, customers interaction, and increased store sales. Factors such as content quality, posting consistency, and interaction with customers are influential in achieving a successful digital marketing strategy. This research provides valuable insights for Nonashope Fashion Store and similar businesses in optimizing their digital marketing strategies through social media to improve business performance and customer satisfaction. Keywords: Digital Marketing Strategy, Social Media, Nonashope Fashion Store